Improving Students’ Metaphor Interpretation: A Conceptual Metaphor Approach to Interpret Metaphors in the Song Titanium (2011) - Muhammad Adam (Ethical Lingua: Journal of Language Teaching and Literature, 2017)
This research is conducted to measure how participants’ understanding to a source domain of metaphor will help them to better interpret metaphor in “Titanium” song by using the Conceptual Metaphor Theory (CMT). The CMT approach is introduced by explicitly explain the characteristic of source domain of metaphor to participants. The participants of this research are 10 students of semester V of Faculty of Letters – University of Balikpapan, all native Indonesian speakers. This research is qualitative research, and uses the participants’ written answer as data source. Based on the data analysis, it is concluded that by understanding the source domain of metaphor, participants have a better and improved understanding in interpreting metaphor. In other words, the participants’ comprehension to the intended message of metaphor is improved.